Tinjauan Peraturan Otoritas Jasa Keuangan Nomor. 31/POJK.05/2016 Terhadap Perlindungan Hukum Bagi Konsumen Dalam Praktik Pegadaian Swasta Sarwah Mandiri - audiana nabilla (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research discusses analyze the related regulation of the financial services authority Number 31 / POJK.05 / 2016 against consumer protection in the practice of private pawnshops Sarwah Mandiri located in Sidoarjo. This research use empirical legal researc. With conceptual approach and statue approach. Data are collected throught interviews. Data are analyzed by descriptive method. The result shows The protection of consumers in the practice of private pawnshops in Sarwah Mandiri is still not fully in accordance with the provisions contained in the rules of the Financial Services Authority Number. 31 / POJK.05 / 2016. First, in terms of private pawnshop licensing, but in practice private pawnshop Sarwah Mandiri has not done the licensing on the grounds of being too complicated and not ready to manage finances formally. Secondly, in the case of pawnshop practices such as keeping the consumer's collateral goods not in accordance with the rules set by the POJK. POJK provides regulations in order to provide protection to consumers who mortgage their collateral in private pawnshops so as not to experience things that are not desirable.